ASSESSING NURSING STAFF SKILLS IN PROVIDING CULTURALLY COMPETENT CARE: A SIMULATION-BASED STUDY - Hessa Hammad AlHarbi, ‏Abdullah Hammad AlHarbi, ‏Aneefah Saud Alshammari, ‏Shuayyi radhi Aldhafeeri, ‏Mohammed Ziyad Alshammari, ‏Tahani metab aldhafeer (Chelonian Research Foundation, 2022)
Cultural competence is essential for quality, equitable nursing care across diverse populations. This study evaluated a customized simulation training focused on building nursing staff skills in providing culturally aware care responsive to patients’ values, beliefs, and needs. Using standardized patient actors from six cultural backgrounds, 148 nurses completed videotaped simulation scenarios assessing cultural aspects. Structured debriefing and self-evaluation followed each simulation. Results showed initially low cultural knowledge and variable person-centered care, with marked improvements in cultural skills, sensitivity and tailored interventions after simulation training. Thematic analysis revealed enhanced nurse self-efficacy, insight into contextual complexities, and commitment to ongoing learning. However, biases and stereotyping persisted for some minority groups. Targeted simulation training shows promise for strengthening nurses’ cultural capabilities, with implications for nursing education and practice quality improvements. Keywords: cultural competence, simulation, nursing education, health disparities